Performance in popular culture - Mazer, Sharon (New York, NY : Routledge, 2024)
"Performance in Popular Culture reveals the intricate relationship between performance and popular culture by exploring how theatrical conventions and dramaturgical tropes have informed the way the social is constructed for popular consumption. Staged as a series of case studies, this book considers the diverse ways the social is imagined and produced in live and mediated performances, in images and texts, in interactive experiences and in cultural institutions. By looking at performance in popular culture, the world we live in becomes more visible, open to investigation and (perhaps) to change. Performance in Popular Culture engages a wide range of disciplines and theoretical frameworks: performance, theatre and cultural studies; comparative literature and media studies; gender and sexuality, critical race and post-colonial theories. Designed for accessibility at an undergraduate level, the case studies make use of visual materials, moving images and texts that are readily available to lecturers and students, to scholars and to the general public"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Popular culture; Performing arts -- Social aspects